2017
DOI: 10.7150/ijms.18037
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane preconditioning inhibits the effects of tissue-type plasminogen activator on brain endothelial cell in an in vitro model of ischemic stroke

Abstract: Tissue-type plasminogen activator (tPA) is the only treatment for ischemic stroke. However, tPA could induce the intracranial hemorrhage (ICH), which is the main cause of death in ischemic stroke patient after tPA treatment. At present, there is no treatment strategy to ameliorate tPA-induced brain injury after ischemia. Therefore, we investigated the effect of pre-treated isoflurane, which is a volatile anesthetic and has beneficial effects on neurological dysfunction, brain edema and infarct volume in ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Although GA did not impact the most severe hemorrhage subtypes (sICH and PH), these findings provide signals about its protective effect against hemorrhage that warrant further exploration. While no definitive explanation regarding the relationship between GA and ICH can be drawn from our data, there are several theoretical possibilities: (1) less patient motion in the setting of GA with more precise intracranial navigation and lower chance of microvascular avulsion; (2) protective effect of anesthetic medications against cerebral ischemic reperfusion injury12–15; (3) reduced pain and agitation with lower chance of blood pressure surges and uncontrolled hypertension, which is an independent risk of HT 16. In addition, hypotension that frequently occurs with GA during thrombectomy may also protect the ischemic tissue against HT after reperfusion.…”
Section: Discussionmentioning
confidence: 88%
“…Although GA did not impact the most severe hemorrhage subtypes (sICH and PH), these findings provide signals about its protective effect against hemorrhage that warrant further exploration. While no definitive explanation regarding the relationship between GA and ICH can be drawn from our data, there are several theoretical possibilities: (1) less patient motion in the setting of GA with more precise intracranial navigation and lower chance of microvascular avulsion; (2) protective effect of anesthetic medications against cerebral ischemic reperfusion injury12–15; (3) reduced pain and agitation with lower chance of blood pressure surges and uncontrolled hypertension, which is an independent risk of HT 16. In addition, hypotension that frequently occurs with GA during thrombectomy may also protect the ischemic tissue against HT after reperfusion.…”
Section: Discussionmentioning
confidence: 88%
“…Accumulating evidence indicates that oxidative stress injures endothelial cells, degrades TJs and contributes to an increase in BBB permeability [ 26 , 39 , 40 ]. It has been demonstrated that BBB disruption might be the a cause rather than a consequence of brain neuron injury and increase the risk of intracerebral hemorrhagic transformation in ischemic stroke [ 4 , 13 ]. However, scientists almost focus their attention on neurons and brain parenchyma during the stroke treatment and overlook the direct BBB protection [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute ischemic stroke, resulting from arterial occlusion in the brain, makes up more than 80% of all the cases [ 1 , 2 ]. Nowadays, thrombolytic therapy with recombinant tissue plasminogen activator (rtPA) continues to be an important medical therapy in the management of acute ischemic stroke within 3–4.5 h of symptom onset [ 3 , 4 ]. However, the cerebral ischemia and reperfusion with thrombolysis treatment may result in serious brain injury, such as intracerebral hemorrhagic transformation (HT), with complex pathological mechanisms, and partially due to the oxidative stress and disruption of the BBB [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous studies, tPA functions as a cytokine that binds to the cell membrane receptors LRP-1 and PDGFRα and triggers the phosphorylation of JNK, P38, NF-κB, thereby inducing the expression of the MMP2 and MMP9 genes ( Hu et al, 2006 ; Ma et al, 2011 ; Cheon et al, 2017 ; Su et al, 2017 ). We further investigated the mechanisms and showed that LRP1 and PDGFRα were not activated in mice that received high-dose rosuvastatin treatment alone and rt-PA treatment alone but were activated in the mice receiving MCAO followed by rt-PA reperfusion for 24 h and MCAO alone.…”
Section: Discussionmentioning
confidence: 61%
“…Previous data have revealed that increased MMP-2, MMP-1, MMP-3, and MMP-9 expression levels might occur via PDGFR-α ( Ma et al, 2011 ) and LRP1 stimulation of the BBB ( Cheon et al, 2017 ; Niego et al, 2017 ). In this study, PPI networks among rt-PA, which is called tissue plasminogen activator (PLAT, tPA) in vivo , and PDGFR-α, LRP1, MMP-2, MMP-1, MMP-3, and MMP-9 were constructed based on the STRING database; this analysis suggested a strong interaction between tPA and LRP1, which showed the highest confidence score.…”
Section: Discussionmentioning
confidence: 99%